Computational study of o-carborane – cucurbit[n]uril inclusion complexes - Polyakova, V.A.; Pustolaikina, I.A. (Академик Е.А. Бөкетов атындағы Қарағанды университетінің баспасы, 2025)
The chemistry of host–guest molecular complexes has garnered considerable attention in recent years. These supramolecular systems exhibit a range of unique properties, including interaction selectivity, reversible binding capabilities, and structural adaptability. Such features make them highly promising candidates for applications in molecular recognition, targeted drug delivery, chemical sensing, and catalysis [1]. Besides conventional host molecules such as cyclodextrins and crown ethers [3-4], a new class of macrocyclic compounds—cucurbiturils—has recently gained significant attention due to its exceptional binding selectivity, remarkable chemical stability across a wide pH range, and distinctive cavity architecture [5].
Keywords: computational study; o-carborane; cucurbit[n]uril; inclusion complexes; molecular interaction